Design and fabrication of low power differential low noise amplifier for WLAN application in deep sub-micron standard CMOS technology / Maizan Muhamad - Maizan, Muhamad (2019)
This thesis presents the design and implementation of low power differential low noise amplifier for wireless local area network application. The operating frequency was designed at 2.4 GHz with a supply headroom of 1.2 V and implemented on Silterra’s 0.13μm RF CMOS process. A detailed methodology that leads to a power efficient design of the circuit is presented. Then, a comprehensive circuit analysis and design methodology of the differential cascode topology, that is the differential Power-Constrained Simultaneous Noise and Input Matching low noise amplifier. A theoretical noise figure optimization using fixed power and physics-based characteristics were used as a design optimization guide. Simultaneous noise and input matching under constrained power was achieved with an extra gate source capacitor while gain enhancement was obtained by employing a capacitive feedback at the cascode transistor. Scattering parameter measurement of differential four-port networks low noise amplifier requires a four-port vector network analyzer. Thus, a measurement technique that enables very accurate measurement for S-parameter of differential low noise amplifier by means of a standard two-port vector network analyzer is presented. This technique involves by terminating two ports at one time while another two ports are measured. Apart from that, a general noise figure de-embedding technique also presented in this thesis. De-embedding noise figure measurement of a differential low-noise amplifier based on the analysis of two gain definitions. The effects of impedance match on noise figure are investigated. The result shows a noise figure of 0.57 dB obtained with the de-embedding technique and 1.2 dB without the de-embedding technique. Noise figure was measured under three different source impedances namely short, open and load. The end-design of the optimized differential low noise amplifier produces a power gain of 17.12dB with a dc power consumption of 7.2mW. A linearity of -10.5 dBm achieved. The LNA has been experimentally verified for its functionality and results a validated peak the performance at 2.4 GHz of operating frequency